Assessment of cognitive impairment in hypertensive individuals attending a tertiary health-care center in metropolitan city: An analytical study - Gode, Nikhil; Kinge, Amol; Shri Karan Jain; Patil, Prashant; Wankhede, Harish; Nimje, Dipti (Asian Journal of Medical Sciences, 2023)
Background: Cognitive impairment is a physiological consequence of ageing. Mostly, after 65 years of age, impairment in the memory and dexterity is common. The various factors for such decline are yet under evaluation. The “Montreal Cognitive Assessment Scale” scoring system is been used in this study. This scale is based on seven domains of cognition. It is developed to improve the chances of early detection of cognitive impairment and it claims to diagnose dementia more efficiently compared to the standard MMSE scale. Aims and Objectives: The present study was conducted to compare the cognition status in hypertensive and normotensive individuals of similar age groups. Materials and Methods: The study participants were the selected patients attending the hypertension (HTN) OPD in Seth GS Medical college and KEM HOSPITAL Parel, Mumbai and among the staff working. Patients with age 30–40 years and blood pressure (BP) <140/90 mm Hg supine position without taking any anti-hypertensive medication. After selection of study subjects, the cognition status was assessed in both groups using the MoCA instrument. The BP was measured in supine posture, after interval of 10 min between each measurement, with the help of Sphygmomanometer. Unpaired “t”-test was applied to test the significance of difference of mean values of MoCA scale. Results: We observed that among hypertensive subjects, comparatively lower MoCA score (mean value: 25.97) was reported. Thirteen (28.88%) study subjects had low MoCA score, whereas 32 (71.11%) hypertensive study subjects had normal MoCA score. Conclusion: Thus, if the HTN is of a longer duration, it may show the poor cognitive performance. However, more such studies are required to know the exact mechanism and to know the critical level of BP which can cause cognitive impairment in long standing cases.